Discussing the use of participatory methods with young people on the move - Santana de Andrade, Glenda; Morrell, Isabel; Freedman, Jane (Frontiers in Human Dynamics, 2026)
IntroductionAt the end of 2023, 117.3 million people were forcibly displaced worldwide. Despite the scale of this phenomenon, young migrants aged 15-25 remain largely invisible in both research and policy, as illustrated by the absence of age-disaggregated data. There is therefore an urgent need for research that centers the multifaceted experiences of young people growing up across borders. Research with populations in a condition of vulnerability and with limited rights also raises critical methodological and ethical questions.MethodsThis paper draws on an ongoing comparative research project with young people on the move, employing participatory research approaches both offline and online. The study combines more traditional qualitative participatory methods with innovative digital and creative tools. Particular attention is paid to the practical and ethical challenges of conducting participatory research with young migrants, including issues of consent, power relations, representation, and safeguarding.ResultsThe findings highlight both the potential and the limits of participatory methods in research with young people in forced migration contexts. Participatory approaches can foster agency, enable more nuanced accounts of lived experiences, and challenge extractive research practices. However, they also reveal significant obstacles, including uneven participation, ethical dilemmas, and institutional constraints that shape what participation can realistically achieve.DiscussionThe paper discusses how participatory research with young people on the move requires constant ethical reflexivity and methodological adaptation. It argues that participatory methods can meaningfully contribute to more ethical and inclusive knowledge production when their limits are explicitly acknowledged. The article contributes to ongoing theoretical and methodological debates on participatory research with young people growing up in a situation of forced migration.